(untitled) - McRobbie, David (Oxford, 1992)
This popular series of readers has now been completely revised andupdated, using a new syllabus and new word structure lists. Readability has beenensured by means of specially designed computer software. Words that are abovelevel but essential to the story are explained within the text, illustrated, andthen reused for maximum reinforcement
Keywords: English language,English; Reading